Parents of children with ASD in Kazakhstan and the choices they make for educational placement of their children - Atshabarova, Aizhan (Nazarbayev University Graduate School of Education, 2020)
Studying the perspectives of parents of children with autism spectrum disorder (ASD) might assist in the effective inclusion of their children in a school setting. The present study investigates the choices parents make, regarding the educational placement of their child with ASD. The main purpose is to understand the parental experience of enrolling their child with ASD into homeschooling, mainstream, or correctional school settings. In addition, the research discusses their recommendation in providing children with ASD with quality education. Bronfenbrenner's ecological systems theory is used as a theoretical framework for the study, underpinning the construction the research....